Treatment of Severe Acute Bacterial Keratitis in Rabbits Using Continuous Topical Ocular Instillation with Norvancomycin - Lin W; Zhao L; Tan Q; Lin D (Dove Medical Press, 2021)
Wenxiang Lin,1,2 Libei Zhao,2 Qian Tan,1,2 Ding Lin1,2 1Department of Ophthalmology, Changsha Aier Eye Hospital, Aier School of Ophthalmology, Central South University, Changsha, People’s Republic of China; 2Department of Ophthalmology, Changsha Aier Eye Hospital, Central South University, Changsha, People’s Republic of ChinaCorrespondence: Ding LinDepartment of Ophthalmology, Changsha Aier Eye Hospital, Aier School of Ophthalmology, Central South University, Changsha, People’s Republic of ChinaTel +86-13787255158Email linding@csu.edu.cnPurpose: Efficacy of norvancomycin (NVCM) through continuous topical ocular instillation drug delivery (CTOIDD) system for treating severe acute bacterial keratitis infection with Staphylococcus aureus was investigated.Methods: Rabbits with bacterial keratitis were treated using CTOIDD with NVCM (n=13), topical NVCM eye drops (n=11), and CTOIDD with saline (n=8). Clinical signs of keratitis in all groups were assessed consecutively for a week. Bacterial quantification of excised corneas was counted on the fourth and eighth days. Histopathologic examinations were performed to assess inflammatory cell infiltration on the eighth day.Results: All signs of bacterial keratitis were alleviated in CTOIDD with NVCM according to criteria, and the CTOIDD-NVCM group had significantly less inflammation than CTOIDD-saline (p< 0.05), and eye drop-NVCM (p< 0.05). Two eyes in the eye drop-NVCM group, four eyes in the CTOIDD-saline group had corneal perforation (CP), while none of the rabbits showed CP in the CTOIDD-NVCM group. Bacterial counts were significantly less in the CTOIDD with NVCM group in comparison to the eye drop-NVCM (p< 0.05), and CTOIDD-saline (p< 0.05) groups. Severe inflammation and marked inflammatory cell infiltration were found in histopathologic examinations in the CTOIDD-saline and eye drop-NVCM groups, while significantly less inflammation was documented in the CTOIDD-NVCM (p< 0.05) group.Conclusion: CTOIDD with NVCM effectively reduced the severity and treated acute bacterial S. aureus keratitis infection in a rabbit model. The presented approach of CTOIDD with NVCM appears to be a promising therapeutic approach for severe acute bacterial keratitis.Keywords: severe acute bacterial keratitis, continuous topical instillation, eye drop, norvancomycin, rabbit eyes